MOBILISASI DINI MENURUNKAN NYERI AKIBAT JAHITAN PERINEUM TINGKAT II PADA IBU POST PARTUM - Ribkha Itha Idhayanti; Asih Warastuti; Bekti Yuniyanti (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2020)
Almost 90% labor experiencing perineal laceration grade II ie wound on the back of the vaginal wall muscle experiencing perineal laceration, but has not reached the anal sphincter. It has an impact on pain or pain during walking, The cause of perineal pain one of them is the lack of early mobilization by the mother, due to pain so afraid to move. Research with respondents mothers who have ruptured perineum grade II Hospital Tidar with a sample of 30 respondents. Showed no correlation results suture perineal pain level grade II with early mobilization 2 hours post partum mothers. Early mobilization resulting in blood circulation and oxygenation of scar tissue becomes better, which stimulates the release of hormones endorphins are helpful to reduce pain. It is expected that health staff nurse midwife or family able to guide and accompany postpartum mothers in particular who had stitches due perineal laceration to perform early mobilization since 2 hours postpartum by moving the arms, legs, move circle ankle, heel lifts, make rilek shank, bend and shifting feet, followed by the right and left oblique, and learn to sit , next learn to walk.